Comparative Biochemical Composition of Natural and Fattened Mud Crab Scylla serrata - Sarower, M. G.; Bilkis, S.; Rauf, M. A.; Khanom, M.; Islam, M. S. (Journal of Scientific Research, 2013)
<p class="MsoNormal" style="margin-top: 0cm; margin-right: 15.55pt; margin-bottom: .0001pt; margin-left: 14.2pt; text-align: justify; text-justify: inter-ideograph; line-height: normal; mso-layout-grid-align: none; text-autospace: none;">The biochemical composition (proteins, lipid, ash and moisture) of different parts of the body (gill, meat, egg) of fattened and natural mud crab Scylla serrata was determined. Twenty four samples of S. serrata (12 from wild & 12 from fattening farm) of different sizes and sexes (half of the sample is male) were used in this study. The mean protein and lipid contents are significantly (p<0.05) higher in fattened crabs than natural in natural crabs regardless of size and sexes. Moisture and ash were higher in natural crab than in fattened ones. The highest and lowest moisture content was noticed in gills and eggs in both natural and fattened crabs. Protein and lipid contents were comparatively higher in eggs than in other body parts. Female crabs contained high protein and lipid than males in both natural and fattened crabs. From the results of this study it may considered that fattened crab might be comparatively superior to natural crabs as they appear to provide higher levels of protein and fat for human nutrition. <p class="MsoNormal" style="margin-top: 0cm; margin-right: 15.55pt; margin-bottom: .0001pt; margin-left: 14.2pt; text-align: justify; text-justify: inter-ideograph; line-height: normal; mso-layout-grid-align: none; text-autospace: none;"> <p class="MsoNormal" style="margin-top: 0cm; margin-right: 15.55pt; margin-bottom: .0001pt; margin-left: 14.2pt; text-align: justify; text-justify: inter-ideograph; line-height: normal; mso-layout-grid-align: none; text-autospace: none;">Keywords: Biochemical composition; Natural and Fattened mud crab; Scylla serrata © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.14082 J. Sci. Res. 5 (3), 545-553 (2013)